ANALISIS KEAMANAN JARINGAN PADA FASILITAS WIFI TERHADAP SERANGAN SNIFFING DI PT DUTA COMPUTER - Silalahi, Putri Rosayanti; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2023)
Technological developments and dependence on WiFi networks have brought many benefits in the business world, including at PT Duta Computer. However, network security is becoming a critical issue as cyber attacks become increasingly complex and sophisticated. One potential attack is a sniffing attack, in which the attacker tries to steal sensitive data that is sent over a WiFi network. This study aims to conduct an in-depth analysis of network security on WiFi facilities at PT Duta Computer against sniffing attacks. The results of this study are expected to provide deeper insight into the level of security of the WiFi network at PT Duta Computer and help companies to identify and address potential security vulnerabilities. By enhancing network security, PT Duta Computer can ensure that sensitive customer data and corporate information remain safe from sniffing attacks.